2014
DOI: 10.1021/es502147y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Functional Groups on Organic Aerosol Cloud Condensation Nucleus Activity

Abstract: Organic aerosols in the atmosphere are composed of a wide variety of species, reflecting the multitude of sources and growth processes of these particles. Especially challenging is predicting how these particles act as cloud condensation nuclei (CCN). Previous studies have characterized the CCN efficiency for organic compounds in terms of a hygroscopicity parameter, κ. Here we extend these studies by systematically testing the influence of the number and location of molecular functional groups on the hygroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
137
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 77 publications
11
137
2
Order By: Relevance
“…Recently, Richards et al (2013) undertook an extensive review of κ values published in the literature and showed that κ org vs. O:C plot has a large degree of scatter. This indicates that other factors, such as phase state (Pajunoja et al, 2015) and molecular structures (Suda et al, 2014) of organic aerosols (OA) other than oxidation state may also play a role in the determination of the OA hygroscopicity.…”
Section: Closure Between Particle Hygroscopicity and Chemical Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Richards et al (2013) undertook an extensive review of κ values published in the literature and showed that κ org vs. O:C plot has a large degree of scatter. This indicates that other factors, such as phase state (Pajunoja et al, 2015) and molecular structures (Suda et al, 2014) of organic aerosols (OA) other than oxidation state may also play a role in the determination of the OA hygroscopicity.…”
Section: Closure Between Particle Hygroscopicity and Chemical Componentsmentioning
confidence: 99%
“…More recently, some studies have been performed to investigate the relationship between particle hygroscopicity and chemical composition in both field measurements and laboratory experiments (Massoli et al, 2010;Wong et al, 2011;Lambe et al, 2011;Rickards et al, 2013;Moore et al, 2012a, b;Suda et al, 2014;Paramonov et al, 2013;Levin et al, 2012). These works specially focused on parametrizing the empirical correlations between the atomic oxygen : carbon (O : C) ratio and organic hygroscopicity parameter (κ) derived from either hygroscopic growth factor (e.g., Wu et al, 2013;Rickards et al, 2013) or cloud condensation nuclei (CCN) activity (e.g., Mei et al, 2013;Wong et al, 2011;Lambe et al, 2011;Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, chemical characteristics of water-soluble organic matter (WSOM) have been intensively investigated, revealing that WSOM predominantly consists of levoglucosan-like species, carboxylic acids, aldehydes, ketones, aliphatic alcohols, and polyacids (Decesari et al, 2000;Peng et al, 2001;Suzuki et al, 2001;MayolBracero et al, 2002;Chan et al, 2005;Psichoudaki and Pandis, 2013). Recently, the important roles of functional groups in water uptake properties were also investigated by both theoretical and experimental approaches (Suda et al, 2014;Petters et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many proposals for reducing representations in which a mixture of 10 000+ different types of molecules (Hamilton et al, 2004) are represented by some combination of their molecular size, carbon number, polarity, or elemental ratios (Pankow and Barsanti, 2009;Kroll et al, 2011;Daumit et al, 2013;Donahue et al, 2012), many of which are associated with observable quantities (e.g., by aerosol mass spectrometry (AMS; Jayne et al, 2000), gas chromatography-mass spectrometry (GC-MS and GCxGC-MS; Rogge et al, 1993;Hamilton et al, 2004)). Molecular bonds or organic functional groups (FGs), which are the focus of this manuscript, can also be used to provide reduced representations for mixtures and have been shown useful for organic mass (OM) quantification, source apportionment, and prediction of hygroscopicity and volatility (e.g., Russell, 2003;Donahue, 2011;Russell et al, 2011;Suda et al, 2014). Examples of property estimation methods include models for purecomponent vapor pressure (Pankow and Asher, 2008;Compernolle et al, 2011), UNIFAC, and its variations for activity coefficients and viscosity (Ming and Russell, 2001;Griffin et al, 2002;Zuend et al, 2008Zuend et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%